Možgani in duh časa - zgodovinsko-biološka skica - Vodušek, David B. (Družboslovne razprave, 2008)
The brain is part of the body which controls all the other organs. It is therefore responsible for the entire functioning of the organism, including behaviour. It also enables 'mental' functions. The text presented is a short outline of understanding the role of the brain through history and today, when the brain has become the object of interest of practically all branches of science that have anything to do with humans and the mentality or abilities and properties we assign to them. At the same time, a warning is issued that despite the big progress made in the past century, especially in the last 20 years, our understanding of the brain is still fragmental. Speaking about a thorough understanding of brain functions will continue to be premature so long as we do not just understand the working of a singular brain, but also the biological dimensions of its connections in social interactions.
Keywords: Brain; Možgani; Kognitivna znanost; Cognitive science; Duševnost; Mentality; Zgodovina; History